Public Private Partnership in Malaysia: The Differences in Perceptions on the Criticality of Risk Factors and Allocation of Risks between the Private and Public Sectors - Usman Ahmad; Yusnidah Ibrahim; Mohd Sobri Minai (International Review of Management and Marketing, 2017)
Public Private Partnership (PPP) was introduced in Malaysia in the 1980s. Malaysian government used this tool for the provision of infrastructure and public services efficiently. However, a few PPP arrangements are under-achieved due to problems in risk identification and management. Therefore, this paper aims to rank risk factors based on criticality. Apart from ranking of risks, this paper provides preferred allocation of critical risk factors. In addition, this study aims to assess the difference of perceptions about the criticality of the risks between contracting parties. First, a few interviews were conducted to screen the risk factors provided in literature and then a set of questionnaires was served upon both private and public sector for the ranking and allocation of risks. To rank risks, a matrix was provided to the respondents and the percentage method was used to allocate the risks. The results of study suggest that 31 out of 44 risk factors are critical and out them 5 critical risk factors should preferably be allocated to private sector. However, a significant difference in perceptions of private and public sector about critically of risks has been identified. The results conclude that the construction and operation stages are critical and for the success of PPP projects both public and private sectors have to improve risk communication to avoid the difference in perception about criticalities of risks.